A decline in youth licensing: a simple delay or the decreasing popularity of automobility?. Issue 1 (2nd January 2021) - Rérat, Patrick
ABSTRACT: In Switzerland, as in several western countries, the share of young adults holding a driving licence has decreased (from more than 70% in 2000 to about 60% in the 2010s). This paper addresses this phenomenon by first conceptualising the driving licence as a set of rules, a right to participate in the automobile system and a rite of passage. Trends in driving licence-holding and their evolution are then analysed, based on the 2000 and 2015 Mobility and Transport Microcensuses. The results show that much of this decrease is due to delaying the age at which young people get their driving licence and not a definitive renunciation. This delay seems less due to a complexification of the rules, an increase in costs and the use of ICT than to an increasingly functional and utilitarian relationship with cars in a context where automobility, although weakening, remains dominant.